19. PENGARUH PEMBERIAN EKSTRAK TEH HIJAU (Camelia sinensis) TERHADAP PENURUNAN KADAR HEMOGLOBIN DAN NILAI HEMATOKRIT PADA TIKUS WISTAR (Rattus norvegicus) The Effect of Green Tea Extract (Camelia sinensis) on Haemoglobin and Hematocrit Levels of Wistar Rat (Rattus norvegicus) - Triva Murtina Lubis (Universitas Syiah Kuala, 2016)
The aim of this study was to determine the effect of green tea (Camelia sinensis) extract on hemoglobin and hematocrit level of Wistar rat (Rattus norvegicus). Sample animals used were 20 rats strain Wistar aged 2.5-3.0 months. Green tea extract was given for 30 days consecutively. Blood collection was conducted via orbitalis sinus for 2 ml using capillary pipette. Rats were fed with standart commercial food (Turbo Feed T.79-4) and aquadest as drinking water ad libitum. This study used completely randomized design (CRD) pattern with 4 treatments and 5 replications. The control group (P0) without any treatment, P1 was given green tea extract 0.045 g/ml/day, P2 was given green tea extract 0.060 g/ml/day, and P3 was given green tea extract 0.075 g/ml/day. Data were analyzed by oneway analysis of variance (Anova). The result showed that mean±SD of hemoglobin levels (g/dl) on each treatment group (P0, P1, P2, and P3) were 11.86±0.55, 12.58±1.40, 11.82±0.69, and 12.50±0.84 respectivey. Mean±SD of hematocrit levels (%) on each treatment group (P0, P1, P2, and P3) were 44.00±4.30, 43.40±1.14, 44.00±1.58, and 42.80±1.79. To conclude, the administration of green tea extract has no effect (P0.05) on haemoglobin and hematocrit levels of Wistar rat. ____________________________________________________________________________________________________________________ Key words: green tea, haemoglobin, haematocrit, Wistar rat